Exploiting the mitogenomes of Apis mellifera subspecies to authenticate the origin of Mediterranean honeys - Honrado, Mónica (2024)
As defined by the Codex Alimentarius, honey is the natural sweet substance produced by honeybees from the nectar of plants.1 This natural product is widely appreciated but is also considered one of the foods most prone to adulteration. The increasing demand for monofloral honey and those with protected designation of origin (PDO) has led to increased fraud by mislabeling botanical and geographical origin.2 Verifying the geographical origin of honey is a challenging endeavor. Recently, attention has been paid to the entomological origin, as it aligns with the geographical patterns of honeybee subspecies. The Mediterranean region is a hot spot of Apis mellifera subspecific diversity shaped by thousands of years of evolution. Although contemporary human-mediated movements of queens have impacted the native subspecific distribution, several PDO honeys specify the subspecies that produce those honeys, thus offering a unique avenue for authentication. As part of the European PRIMA project MEDIBEES, we aim to develop a DNA-metabarcoding approach to authenticate honey's entomological origin, focusing on mitochondrial lineages A, M, C, and O. To achieve this, the DNA of 1280 honeybees representing 16 subspecies and the four lineages (A.m. sahariensis, A.m. intermisa, A.m. siciliana, A.m. ruttneri, A.m. iberiensis, A.m. ligustica, A.m. macedonica, A.m. adami, A.m. cecropia, A.m. cypria, A.m. caucasica, A.m. meda, A.m. anatoliaca, A.m. syriaca, A.m. jemenitica, A.m. lamarcki) was extracted, and their whole genomes were sequenced. The MitoZ software was used to assemble the mitochondrial genomes, resulting in 769 mitochondrial genomes successfully assembled. Subsequently, each of these genomes was aligned individually with a reference genome using MEGA software, and mitogenomes not specific to Apis mellifera were discarded. Of these, only the mitogenomes corresponding to the native ancestry were retained, resulting in a final set of 355 mitogenomes in the database. A phylogenetic analysis was conducted with the final 355 mitochondrial sequences, revealing four distinct clusters corresponding to the four maternal lineages. This dataset was used for calculating the fixation index (FST) pairwise values, and a sliding window of 400 bp was used to identify single nucleotide polymorphisms (SNPs) that effectively differentiate (FST>0.98) the four lineages, enabling the identification of promising regions for primer design. This work resulted in the discovery of three promising regions for discriminating the four maternal lineages: one in the COI gene, one in the ND1 gene, and one in the CYTB gene (Fig. 1).